BecA has a key role for Africa to drive its own agricultural research agenda - International Livestock Research Institute (International Livestock Research Institute, 2010)
On 5 November 2010, David Collins, Canadian High Commissioner to Kenya spoke at the official Launch of the Biosciences eastern and Central Africa (BecA) Hub. Representing the founding funder of the Hub, he noted that BecA is conducting important research that will help address key agricultural issues, including those facing small-scale African farmers, the majority of whom are women. Our investment in BecA has supported the construction of new and renovation of existing facilities, including laboratories. With the completion of construction, the Hub is now in full operation, with a number of significant research programs underway, and quickly gaining regional and international recognition as a world-class facility to support capacity for Biosciences in Africa. In conclusion he said “It is exciting to see the birth of a hub that will play a key role in ensuring that Africa drives its own agenda in regards to Agriculture and strengthen the research pillar of the Comprehensive Africa Agriculture Development Program”.